Case Report: Abscopal effect and long-term survival in a PD-L1 negative NSCLC patient treated with radiotherapy and immuno-chemotherapy - Wen, Qiang; Wang, Weiqi; Zhang, Ke; Pan, Chunguo; Liu, Zhihua; Wang, Lei (Frontiers in Immunology, 2025)
We present a case of a 68-year-old male with advanced non-small cell lung cancer (NSCLC), PD-L1 negative and driver gene negative, who exhibited a significant abscopal effect following radiotherapy combined with systemic immunotherapy (sintilizumab) and chemotherapy. The patient achieved complete remission (CR) of intracranial metastases without cranial irradiation, suggesting a systemic immune response triggered by the combination of radiotherapy and immunotherapy. This case highlights the potential of radiotherapy combined with immuno-chemotherapy to induce abscopal effects, even in PD-L1 negative patients, and underscores the importance of further investigation into this therapeutic strategy. This case challenges traditional paradigms in NSCLC management and aligns with emerging theragnostic approaches that integrate localized treatment with systemic immune modulation.